Step 1: Splitting the fraction.
We rewrite the given integral:
\[
I = \int \frac{\sin^2 x}{\sin^2 x \cos^2 x} dx - \int \frac{\cos^2 x}{\sin^2 x \cos^2 x} dx
\]
Simplifying each term separately:
\[
I = \int \frac{1}{\cos^2 x} dx - \int \frac{1}{\sin^2 x} dx
\]
Step 2: Recognizing standard integral forms.
Using the standard integral formulas:
\[
\int \sec^2 x dx = \tan x + C, \quad \int \csc^2 x dx = -\cot x + C
\]
Thus,
\[
I = \tan x + \cot x + C
\]
Thus, the correct answer is (A) \( \tan x + \cot x + C \).